Computational insights for the hydride transfer and distinctive roles of key residues in cholesterol oxidase. Issue 1 (December 2017) - Yu, Li-Juan; Golden, Emily; Chen, Nanhao; Zhao, Yuan; Vrielink, Alice; Karton, Amir
Abstract Cholesterol oxidase (ChOx), a member of the glucose-methanol-choline (GMC) family, catalyzes the oxidation of the substratevia a hydride transfer mechanism and concomitant reduction of the FAD cofactor. Unlike other GMC enzymes, the conserved His447 is not the catalytic base that deprotonates the substrate in ChOx. Our QM/MM MD simulations indicate that the Glu361 residue acts as a catalytic base facilitating the hydride transfer from the substrate to the cofactor. We find that two rationally chosen point mutations (His447Gln and His447Asn) cause notable decreases in the catalytic activity. The binding free energy calculations show that the Glu361 and His447 residues are important in substrate binding. We also performed high-level double-hybrid density functional theory simulations using small model systems, which support the QM/MM MD results. Our work provides a basis for unraveling the substrate oxidation mechanism in GMC enzymes in which the conserved histidine does not act as a base.